Large-grained Sb2S3 thin films with Sn-doping by chemical bath deposition for planar heterojunction solar cells. (September 2018) - Chalapathi, U.; Poornaprakash, B.; Ahn, Chang-Hoi; Park, Si-Hyun
Abstract: Herein, the growth of large-grained and compact Sb2 S3 thin films with good electrical properties by Sn doping using a chemical bath deposition (CBD) and annealing approach is detailed. Sn-doped Sb2 S3 thin films were prepared using the CBD method with SbCl3, SnCl2 .2H2 O, and Na2 S2 O3 as source materials, and ethylenediamine tetraacetic acid (EDTA) as the complexing agent at 40 ° C for 3 h followed by annealing at 250 °C for 30 min under Ar ambience. Un-doped Sb2 S3 films exhibited an orthorhombic crystal structure with lattice parameters of a = 1.142 nm, b = 0.381 nm, and c = 1.124 nm, crystalline grain sizes of 100 nm, a direct optical band gap of 1.70 eV, p-type electrical conductivity with high electrical resistivity, and low hole mobility. With Sn doping, a significant increase in the grain size of the films from 6 to > 10 μ m was observed with increasing Sn content from 1.0 to 5.5 at% followed by a decrease in the grain size. The direct optical band gap of the films was 1.71–1.72 eV. By varying Sn at%, the electrical resistivity of the films decreased, and hole mobility increased from 117 to 205 cm 2 V −1 s −1 up to 5.5 at% and decreased to 166 cm 2 V −1 s −1 at 7.2 at%. With the addition of 1.0–5.5 at% Sn in the Sb2 S3 films, the grain growth and electrical properties of the films were drastically enhanced, which is beneficial for the fabrication of planar heterojunction solar cells.